Hypocalcemia in sepsis: analysis of the subcellular distribution of Ca2+ in septic rats and LPS/TNF-α-treated HUVECs - Wencheng He; Lei Huang; Hua Luo; Yang Zang; Youzhong An; Weixing Zhang (Journal of Infection in Developing Countries)
Introduction: Hypocalcemia has been widely recognized in sepsis patients. However, the cause of hypocalcemia in sepsis is still not clear, and little is known about the subcellular distribution of Ca2+ in tissues during sepsis.